Meningkatkan Motivasi Belajar Siswa Sekolah Dasar Pada Muatan IPA Menggunakan Model Problem Based Learning dan Student Teams Achievement Division - Hilmalia Andira Putri; Maimunah . (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This study identifies the issue of low student motivation in science subjects among fifth-grade students at SDN Mawar 8 Banjarmasin. Contributing factors include students' lack of enthusiasm, low curiosity, and passive attitudes during the learning process. To address this problem, the study implemented Problem Based Learning (PBL) and Student Teams Achievement Division (STAD) models. The objective of the research was to analyze students' learning motivation in science subjects. The research utilized Classroom Action Research (CAR) conducted over four sessions. The subjects of the study were 12 fifth-grade students from SDN Mawar 8 Banjarmasin during the second semester of the 2023/2024 academic year. The data collected were qualitative, obtained through observations of student motivation. The results indicate that teacher activity improved from a score of 17 in the first meeting to 30 in the fourth meeting. Student activity also showed a significant increase from 33% in the first meeting to 92% in the fourth meeting, reaching very active criteria. Students' learning motivation improved from 25% in the first meeting to 100% in the fourth meeting, achieving very high criteria. Additionally, student learning outcomes improved from 17% to 100%.